Effects of transitioning from conventional methods to liquid‐based methods on unsatisfactory Papanicolaou tests: Results from a multicenter US study. Issue 10 (8th May 2013) - Owens, Christopher L.; Peterson, Dan; Kamineni, Aruna; Buist, Diana S. M.; Weinmann, Sheila; Ross, Tyler R.; Williams, Andrew E.; Stark, Azadeh; Adams, Kenneth F.; Field, Terry S.
Abstract : BACKGROUND: Papanicolaou (Pap) testing has transitioned from conventional preparations (CPs) to liquid‐based preparations (LBPs) because of the perceived superiority of LBPs. Many studies conclude that LBPs reduce unsatisfactory Pap tests; however, some believe that the evidence substantiating this claim is weak. The authors studied the effect of the transition from CPs to LBPs on the proportion of unsatisfactory Pap tests in 4 health care systems in the United States participating in the National Institutes of Health‐funded Screening Effectiveness and Research in Community‐Based Healthcare (SEARCH) project. METHODS: The study cohort consisted of 548, 174 women ages 21 to 65 years who had 1443, 725 total Pap tests between 2000 and 2010. Segmented regression analysis was used to estimate the effect of adopting LBPs on the proportion of unsatisfactory Pap tests after adjusting for age. RESULTS: Three sites that implemented SurePath LBP experienced significant reductions in unsatisfactory Pap tests (estimated effect: site 1, −2.46%; 95% confidence interval [CI], −1.47%, −3.45%; site 2, −1.78%; 95% CI, −1.54%, −2.02%; site 3, −8.25%; 95% CI, −7.33%, −9.17%). The fourth site that implemented ThinPrep LBP did not experience a reduction in unsatisfactory Pap tests. The relative risk of an unsatisfactory Pap test in women aged ≥50 years increased after the transition to LBPs (SurePath: relative risk, 2.1; 95% CI, 1.9‐2.2; ThinPrep: relative risk, 1.7; 95% CI, 1.5‐2.0). CONCLUSIONS: The observed changes in the proportion of unsatisfactory Pap tests varied across the participating sites and depended on the type of LBP technology, the age of women, and the rates before the implementation of this technology. Cancer (Cancer Cytopathol) 2013;121:568–575. © 2013 American Cancer Society. Abstract : Observed changes over time in the proportion of unsatisfactory Papanicolaou tests after conversion to liquid‐based technology vary across participating sites and depend on the type of technology used. The changes are influenced by the proportion of unsatisfactory studies before the implementation of liquid‐based technology.